Purinergic Signalling and Endothelium - Burnstock, Geoffrey (Current Vascular Pharmacology, 2016)
Purinergic signalling is involved in the control of vascular tone and remodelling. Endothelial cells release purines and pyrimidines in response to changes in blood flow (evoking shear stress) and hypoxia. They then act on P2Y, P2X and P1 receptors on endothelial cells leading to release of EDRF mediated by nitric oxide and prostaglandins and EDHF, resulting in vasodilatation. The therapeutic potential of purinergic compounds for the treatment of vascular diseases, including hypertension, ischaemia, atherosclerosis, migraine and coronary artery and diabetic vascular disease as well as vasospasm is discussed.
Keywords: ischaemia